2021
DOI: 10.1021/acs.cgd.1c00666
|View full text |Cite
|
Sign up to set email alerts
|

Cold Crystallization and Polymorphism Triggered by the Mobility of the Phenyl Group in Alkyl Azo Dye Molecules

Abstract: The thermal behavior, including the cold crystallization, of alkylderivatized Sudan III (1-[4-(phenylazo)phenylazo]-2-naphthol), SD3-OCn, was investigated. Its structural flexibility due to the two azo groups caused the formation of plural crystal structures, which further resulted in complex cold crystallization. A metastable nonflat structure and a thermodynamically stable flat structure resulted in the two sets of crystallization and melting behavior during the heating process. Further, the change in the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…While the cold crystallization of polymers is well documented, [35][36][37] reports on the cold crystallization of small molecules are scarce. [38][39][40][41] The existing literature suggests that the rotation of aromatic groups hinders crystallization upon cooling, and that molecular flexibility is an important factor for cold crystallization. Nonetheless, the cold crystallization of Schiff-base nickel complexes without aromatic groups, such as OC12-salpn, has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…While the cold crystallization of polymers is well documented, [35][36][37] reports on the cold crystallization of small molecules are scarce. [38][39][40][41] The existing literature suggests that the rotation of aromatic groups hinders crystallization upon cooling, and that molecular flexibility is an important factor for cold crystallization. Nonetheless, the cold crystallization of Schiff-base nickel complexes without aromatic groups, such as OC12-salpn, has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the cold crystallization of small molecules, the mobility of the aromatic rings is considered a factor in supercooling. 18 In previous studies, the diketopyrrolopyrrole (DPP) pigment and azo dye molecules were found to exhibit cold crystallization. 18,19 These molecules have rotatable aromatic rings, and the mobility of the rings leads to polymorphism and/or non-uniform crystallization, resulting in a slow rate of crystallization, supercooling, and cold crystallization.…”
Section: Introductionmentioning
confidence: 99%
“… 18 In previous studies, the diketopyrrolopyrrole (DPP) pigment and azo dye molecules were found to exhibit cold crystallization. 18,19 These molecules have rotatable aromatic rings, and the mobility of the rings leads to polymorphism and/or non-uniform crystallization, resulting in a slow rate of crystallization, supercooling, and cold crystallization. In the study of the azo molecule, the mobility of the aromatic ring was confirmed as polymorphism and disorder in the single-crystal structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16] Small molecules oen adopt a low crystallization temperature; therefore, they are suitable for the storage of low-temperature waste heat in society. 17,18 In addition to heat storage, photochemical energy storage has attracted attention. Photochromic molecules are oen used in energy storage.…”
Section: Introductionmentioning
confidence: 99%